Menolak Instrumentasi Negara: Ruang Gerak Pesantren dalam Otonomi Daerah - Asep Suryana (Antropologi Indonesia, 2001)
The implementation of local government policies during the New Order era has weakened Pesantren as local and Islamic education institution. The weakening is due to, firstly, the instructive position of central government to its local subordinates implying that this later apparatus be the instrument of gaining its target. Secondly, the head of local government as solely powerful figure in local structure has been decisive in many local policies. This local political situation has also implied a centralization of Islamic education policies during the era. The discussed cases of two Pesantren in two different districts in this article reveal that regional autonomy will be presumably strengthening this Islamic education institution.